2017
DOI: 10.1186/s12940-017-0284-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ambient temperature on type-2-diabetes: case-crossover analysis of 4+ million GP consultations across England

Abstract: BackgroundGiven the double jeopardy of global increases in rates of obesity and climate change, it is increasingly important to recognise the dangers posed to diabetic patients during periods of extreme weather. We aimed to characterise the associations between ambient temperature and general medical practitioner consultations made by a cohort of type-2 diabetic patients. Evidence on the effects of temperature variation in the primary care setting is currently limited.MethodsCase-crossover analysis of 4,474,94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 31 publications
3
40
0
2
Order By: Relevance
“…Studies from the United States [ 2 4 ] and Sydney, Australia [ 5 ] found positive associations between temperature and DM-related complications and mortality, while studies from the Philippines [ 6 ] and China [ 7 , 8 ] found increased DM mortality at both high and low temperatures. Climate change, which is leading to higher average global temperatures [ 10 ], and the rising prevalence of DM have been suggested to pose a “dual threat” in increasing the disease burden [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from the United States [ 2 4 ] and Sydney, Australia [ 5 ] found positive associations between temperature and DM-related complications and mortality, while studies from the Philippines [ 6 ] and China [ 7 , 8 ] found increased DM mortality at both high and low temperatures. Climate change, which is leading to higher average global temperatures [ 10 ], and the rising prevalence of DM have been suggested to pose a “dual threat” in increasing the disease burden [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Case-crossover studies [ 18 ] have been used to good effect to identify triggers of other acute health events (e.g. [ 19 21 ]), and researchers have begun adopting this design to investigate episodic flare-ups of OA [ 22 ]. However, there are a number of challenges and uncertainties, including the ability to identify and recruit individuals at risk of flare-ups to online data collection, efficient and timely capture of these relatively short-lived and currently ill-defined events, and the ascertainment of relevant, transient exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Type-2 diabetic and obese individuals are also at risk of ill-health during high ambient temperatures. In a temperate region (Köppen system classification: temperate, Cfb) English type-2 diabetic patients were found to be at an increased odds of presenting to their medical practitioner on days of high ambient temperature and these odds were elevated for diabetic patients with cardiovascular comorbidities [54].…”
Section: Chronic Conditionsmentioning
confidence: 99%